Do Profit-Sharing Rate, Promotion Media, Location, And Service Facilities Affect Muslim Decisions To Use Islamic Banks? - Nur Rizqi Febriandika (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
The majority of Indonesian people are Muslim, making Indonesia a potential market in the development of Islamic banking. The purpose of this study was to determine whether profit-sharing rate, promotion media, location, service facilities affect the decisions of the Muslim community to use Islamic banks. This type of research is quantitative research, which uses the method of structural equity modelling (SEM). The large sample size for the SEM method is based on the number of indicators in the variable due to the enormous population size, namely Muslims in Indonesia. The number of respondents in this study was 214 people. The results of this study indicate that profit-sharing rate, promotion media, location, service facilities do not affect the decisions of the Muslim community to use Islamic banks. Muslims are more likely to choose Islamic banks because of the halal label than other factors. Factors that generally make customers use conventional banks do not apply to Islamic banks. This research can be a reference or a reference for Islamic banks in making policies. Variables that are proven to have no effect can be eliminated in making policies to increase Islamic bank customers.